A novel and fast voltage estimation scheme for assessment of power system component outages. Issue 4 (1st July 2014) - Masoud Fatemi, Seyed; Abedi, Mehrdad; Vahidi, Behrooz; Abedi, Sajjad; Rastegar, Hassan
Abstract : Purpose: – The purpose of this paper is to pursue two following main goals: first, theorizing a new concept named as equivalent bus load in order to make a promising simplification over power system analysis. Second, proposing an outstanding fast and simple approach based on introduced concept for voltage estimation after multiple component outages while satisfying required accuracy. Design/methodology/approach: – Equivalent load bus theory introduces three transfer matrices that describe power system topology. Mentioned matrices could be calculated simply after system reconfiguration without matrix inversion. Using transfer matrices a large-scale power system can be modeled by a simple two-bus power system from the viewpoint of any desired bus so that load flow calculation leads to same value. The analysis of simplified power system yields to extract a new incremental model based on equivalent bus load theory that will be distinguished as an outstanding fast method for voltage estimation aim. Findings: – A deep study for fast voltage estimation aim is dedicated to evaluate proposed method from the accuracy and quickness point of view and the outcomes are compared to a well-known method as Distribution Factors (DF). Results and computational times unveil that presented approach is more accurate and much faster. Originality/value: – A novel and new fast voltage estimation method for assessment of power system component outages is introduced.